The Erosion of Public Space and the Collapse of Agoras: An Evaluation of the Gated Communities in Istanbul - Şahin, Kadir (Journal of History Culture and Art Research, 2017)
When urban life is considered in its natural state it is easy to say that, it is a spatial synergy based on diversity. However, the increasing ongoing effort of 'urban planning' became a reality that battles with the natural state of the city. Especially when the presentations of 'gated community' in late modern cities considered, it can be seen that traditional modern cities contain major changes in terms of its nature. It can be said that the most remarkable points with the emergence of those sorts of changes are the changes in terms of private and public spaces. Thus, with the emergence of the new housing forms where the natural city security is cancelled, the values of the street and neighborhood life 'in traditional modern city' became a factor of danger and uncertainty. The social relations that can be expressed as 'urban uncanny', 'randomness', 'deformities' and 'routines' of the 'traditional modern city' life gradually became a reality that is based on distrust and danger. However, in the agoras (intermediate spaces) of the 'traditional modern city' all the factors in the name of 'gated community' which enable these sorts of interactions are changed into public passivity. On that sense, the new urban areas (gated communities) which had been formed because of the security concerns are changing and making agoras non-functional, which results in the cancellation of the nature of the city and the natural security. In this paper, we are discussing the sociological reasons behined the emerge of 'public passivity' and the collapse of the agoras (its neighborhood and streets) of the traditional modern city through the residences of 'gated communities in Istanbul'.